Estimating survival rates after ovarian cancer among women tested for BRCA1 and BRCA2 mutations. (19th April 2013) - Narod, SA; Moody, JRK; Rosen, B; Fan, I; Risch, A; Sun, P; McLaughlin, JR
Abstract : Several studies have reported that women with ovarian cancer and a BRCA1 or BRCA2 mutations have better survival than women with ovarian cancer and no mutation. Potential reasons for this include possible differences in histologic subtype, stage, grade and response to chemotherapy, but some of the difference in survival may be due to systematic bias, i.e. a difference in survival rates for women who do and who do not undergo genetic testing. We estimated the survival rate in 1423 ovarian cancer patients from Ontario who had genetic testing and compared this with the survival rate for all 3367 ovarian cancer patients from the province from whom the tested sample was derived. Tested women had a 10‐year survival of 54.5%, compared to 35.8% for all patients in the province. We evaluated the extent to which three different methods of adjustment eliminated the observed difference. The adjusted rates for the tested cohort were closer to the provincial average, but each adjustment method resulted in a modest over‐estimate of 10‐year survival, ranging from 6.1% to 10.0%. The mortality advantage for tested women was due, in part, to a lower than expected mortality rate of tested women in the period following genetic testing.